2019
DOI: 10.1093/jxb/erz494
|View full text |Cite
|
Sign up to set email alerts
|

Storing carbon in leaf lipid sinks enhances perennial ryegrass carbon capture especially under high N and elevated CO2

Abstract: By modifying two genes involved in lipid biosynthesis and storage [cysteine oleosin (cys-OLE)/diacylglycerol O-acyltransferase (DGAT)], the accumulation of stable lipid droplets in perennial ryegrass (Lolium perenne) leaves was achieved. Growth, biomass allocation, leaf structure, gas exchange parameters, fatty acids, and water-soluble carbohydrates were quantified for a high-expressing cys-OLE/DGAT ryegrass transformant (HL) and a wild-type (WT) control grown under controlled conditions with 1–10 mM nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…It was suggested earlier that carbon metabolism could trigger TAG accumulation in plants. This phenomenon was reported previously for forage grasses [32,57,58].…”
Section: Gas Exchange Stomata and Photosynthetic Performancesupporting
confidence: 87%
“…It was suggested earlier that carbon metabolism could trigger TAG accumulation in plants. This phenomenon was reported previously for forage grasses [32,57,58].…”
Section: Gas Exchange Stomata and Photosynthetic Performancesupporting
confidence: 87%
“…The increase in total plant DW relative to total plant N and the resultant decrease in tissue N per unit DW at elevated CO 2 has been termed ‘N dilution’ and has been linked to increased accumulation of non‐structural carbohydrates and plant secondary compounds (Taub and Wang ). In some cases, elevated CO 2 can increase photosynthesis in the short term, but if photosynthate utilisation is inadequate, a source sink imbalance can arise, leading to end‐product (carbohydrate) accumulation and subsequent down‐regulation of photosynthesis linked to lower ribulose‐1,5‐bisphosphate carboxylase/oxygenase (Rubisco) concentration and activity (Ainsworth and Rogers , Zheng et al , Beechey‐Gradwell et al ). In their Summary, Bloom et al () stated that ‘hundreds of papers’ support their proposal that rising atmospheric CO 2 concentrations inhibit malate production in chloroplasts and thus impede assimilation of NO 3 − into protein in shoots of C 3 plants.…”
Section: Response To Bloom Et Almentioning
confidence: 99%
“…However, the cost associated with production of fuels and other bioproducts from plant biomass is relatively high, which has been a major constraint on the widespread adoption of grasses as sources of feedstock to produce biofuels or bioproducts (Hill et al , 2006; Kumar, Long and Singh, 2018). Previous work showed that C4 grasses can be genetically engineered for increased fatty acid production, resulting in biomass with high oil content (Huang, Long and Singh, 2015; Huang et al , 2016; Wang, 2016; Zale et al , 2016; Beechey-Gradwell et al , 2020; Mitchell et al , 2020; Parajuli et al , 2020), which increases their value as biofuels. Genetically engineering high-biomass grasses to accumulate valuable bioproducts that require minimal processing post-harvest is a desirable way forward, but has many challenges.…”
Section: Introductionmentioning
confidence: 99%